2021
DOI: 10.1007/s10557-021-07261-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prophylaxis of Post-pericardiotomy Syndrome in Cardiac Surgery Patients: a Systematic Review

Abstract: Purpose Post-pericardiotomy syndrome (PPS) is a common complication of cardiac surgery. This systematic review aimed to investigate the efficacy of colchicine, indomethacin, and dexamethasone in the treatment and prophylaxis of PPS. Methods Literature research was carried out using PubMed. Studies investigating ≥ 10 patients with clinically PPS treated with colchicine, dexamethasone, and indomethacin and compared with placebo were included. Animal or in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…These changes in ejection fraction showed recovery or improvement 1 year after the operation. These results suggested that the decline in ejection fraction in patients receiving Inspiris and Intuity was due to adhesion from pericardiotomy and postpericardiotomy syndrome 11 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These changes in ejection fraction showed recovery or improvement 1 year after the operation. These results suggested that the decline in ejection fraction in patients receiving Inspiris and Intuity was due to adhesion from pericardiotomy and postpericardiotomy syndrome 11 …”
Section: Discussionmentioning
confidence: 91%
“…These results suggested that the decline in ejection fraction in patients receiving Inspiris and Intuity was due to adhesion from pericardiotomy and postpericardiotomy syndrome. 11 Replacement of the aortic valve with a prosthesis result in alteration of mitral annular motion due to anatomical changes in the aortic-mitral fibrous continuity. 12,13 Previous reports showed that the existence of aortic prosthesis results in a greater reduction in anterior annulus length compared to posterior annulus suggesting mechanical compression by the prosthetic valve.…”
Section: Resultsmentioning
confidence: 99%